A comparative study of biocarbon reinforced polyoxymethylene and polyamide: Materials performance and durability. (January 2022) - Andrzejewski, Jacek; Aniśko, Joanna; Szulc, Joanna
Abstract: Polyoxymethylene (POM)- and polyamide 6 (PA6)-based biocomposites were investigated in order to evaluate the reinforcing efficiency of a biocarbon filler (BioC). Both types of composites were prepared by melt-blending extrusion with 10, 20, and 30 wt% of BioC. Samples were prepared by the injection molding method and subjected to a detailed analysis consisting of mechanical and thermo-mechanical tests, thermal analysis, and microscopic observations. In order to evaluate the durability of the composite, accelerated thermal and hydrothermal tests were performed. The results reveal significant differences between PA6- and POM-based composites, both in terms of mechanical properties and fracture mechanisms. Water uptake tests confirmed the strong hygrophytic character of PA6-based composites; for the hydrophobic POM-based composites, the increased water uptake suggests strong moisture adsorption of the biocarbon. A heat aging test revealed that the exposure to elevated temperatures did not lead to a significant deterioration of properties for POM- and PA6-based materials.